М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
avatarmeri15
avatarmeri15
20.05.2020 04:25 •  Алгебра

4 sin 45° × tg 30°×ctg30°-cos45°

👇
Ответ:
a24027679
a24027679
20.05.2020

\frac{3 \sqrt{2} }{2}

Объяснение:

4 \times \frac{ \sqrt{2} }{2} \times \tan(30) \times \frac{1}{ \tan(30) } - \frac{ \sqrt{2} }{2} \\ 2 \sqrt{2} - \frac{ \sqrt{2} }{2} \\ \\ \frac{3 \sqrt{2} }{2 }

4,4(22 оценок)
Открыть все ответы
Ответ:
vera0503
vera0503
20.05.2020

1. 3х - 3

2. -11

3. 7х - 1

4. -20

5. 5

6. 2х - 9

7. 2

8. 7х - 10

9. -19

10. 7х - 5

Объяснение:

1. 3(х+4) - (3-х) - х - 4 = 3х + 4 - 3 + х - х - 4 = 3х - 3

2. x + 4 - 5(2-х) - (5+1)х - 5 = х + 4 - 10 + 5х - 5х - х - 5 = 4 - 10 - 5 = -11

3. 4(x+4) - 4(3-х) - x - 5 = 4х + 16 - 12 + 4х - х - 5 = 4х + 4х - х + 16 - 12 - 5 = 7х - 1

4. x + 2 - 4(5-х) - (4+1)х - 2 = х + 2 - 20 + 4х - 4х - х - 2 = -20

5. 2(x+4) - (1-x) - (1+2)х - 2 = 2х + 8 - 1 + х - х - 2х - 2 = 8 - 1 - 2 = 5

6. x + 2 - 2(5-х) - x - 1 = х + 2 - 10 + 2х - х - 1 = 2 - 10 - 1 + 2х = -9 + 2х = 2х - 9

7. 4(x+2) - (1-x) - (1+4)х - 5 = 4х + 8 - 1 + х - х - 4х - 5 = 8 - 1 - 5 = 2

8. 4(х+2) - 4(4-x) - x - 2 = 4х + 8 - 16 + 4х - х - 2 = 4х + 4х - х + 8 - 16 - 2 = 7х - 10

9. 3(х+1) - 4(5-х) - (4+3)х - 2 = 3х + 3 - 20 + 4х - 4х - 3х - 2 = 3 - 20 - 2 = -19

10. 3(x+3) - 5(2-х) - x - 4 = 3х + 9 - 10 + 5х - х - 4 = 3х + 5х - х + 9 - 10 - 4 = 7х - 5

4,8(70 оценок)
Ответ:
ulyanagrab333
ulyanagrab333
20.05.2020

1. 3х - 3

2. -11

3. 7х - 1

4. -20

5. 5

6. 2х - 9

7. 2

8. 7х - 10

9. -19

10. 7х - 5

Объяснение:

1. 3(х+4) - (3-х) - х - 4 = 3х + 4 - 3 + х - х - 4 = 3х - 3

2. x + 4 - 5(2-х) - (5+1)х - 5 = х + 4 - 10 + 5х - 5х - х - 5 = 4 - 10 - 5 = -11

3. 4(x+4) - 4(3-х) - x - 5 = 4х + 16 - 12 + 4х - х - 5 = 4х + 4х - х + 16 - 12 - 5 = 7х - 1

4. x + 2 - 4(5-х) - (4+1)х - 2 = х + 2 - 20 + 4х - 4х - х - 2 = -20

5. 2(x+4) - (1-x) - (1+2)х - 2 = 2х + 8 - 1 + х - х - 2х - 2 = 8 - 1 - 2 = 5

6. x + 2 - 2(5-х) - x - 1 = х + 2 - 10 + 2х - х - 1 = 2 - 10 - 1 + 2х = -9 + 2х = 2х - 9

7. 4(x+2) - (1-x) - (1+4)х - 5 = 4х + 8 - 1 + х - х - 4х - 5 = 8 - 1 - 5 = 2

8. 4(х+2) - 4(4-x) - x - 2 = 4х + 8 - 16 + 4х - х - 2 = 4х + 4х - х + 8 - 16 - 2 = 7х - 10

9. 3(х+1) - 4(5-х) - (4+3)х - 2 = 3х + 3 - 20 + 4х - 4х - 3х - 2 = 3 - 20 - 2 = -19

10. 3(x+3) - 5(2-х) - x - 4 = 3х + 9 - 10 + 5х - х - 4 = 3х + 5х - х + 9 - 10 - 4 = 7х - 5

4,7(20 оценок)
Это интересно:
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ